Internationalization Of Higher Education In The Light Of Some Indicators - ElÃas, Silvina; Morresi, Silvia; Tombolato, Ana MarÃa (European Scientific Journal, ESJ, 2016)
At all the conferences held by the actors involved in the provision of Higher Education internationalization is seen as a new and indispensable dimension which must be considered within the mission of Higher Education Institutions (HEIs). Several reasons, of national as well as international nature, support this recommendation. Among the first ones, the development of human resources; the creation of strategic alliances; the generation of income/commerce and transactions; the construction of Nation and institutions; social and cultural development; and mutual understanding are worth mentioning. Whereas the enhancement of the international image and reputation; quality improvement; human resources development; income generation; the creation of strategic alliances; research and knowledge production are among the institutional reasons that lead to the internationalization of HEIs (Knight, 2005). Likewise there are several different higher education internationalization modalities that may be adopted by a HEI such as students and teachers mobility; distant education or education delivered by institutions located abroad; the design and strengthening of strategies and programs which are oriented to regional integration and international cooperation; formation of nets and projects for international cooperation and the celebration of inter institutional alliances, and the incorporation of the international dimension in the study programs. This presentation intends to assess the degree of internationalization of three Argentine HEIs by means of a group of indicators.